Pengaruh Model Pembelajaran Tari Bambu Terhadap Kemampuan Memahami Isi Cerita Lisan Siswa Kelas V SDN Mejoyolosari Kabupaten Jombang - Dwinata, Anggara Dwinata; Ahmad Faizi; Kemil Wachidah; Dodik Eko Yulianto; Rista Febi Wulandari (Discovery, 2024)
Indonesian is an important aspect in developing speaking, reading, writing and listening skills. Understanding the contents of oral stories in Indonesian language subjects is a synthesis between aspects of reading and speaking as a form of comprehensive understanding in training precision and accuracy in understanding the contents of stories. This research aims to describe the influence of the bamboo dance learning model on the ability to understand the co Indonesian is an important aspect in developing speaking, reading, writing and listening skills. Understanding the contents of oral stories in Indonesian language subjects is a synthesis between aspects of reading and speaking as a form of comprehensive understanding in training precision and accuracy in understanding the contents of stories. This research aims to describe the influence of the bamboo dance learning model on the ability to understand the contents of oral stories of class V students at SDN Mejoyolosari Jombang Regency. The research sample was all 18 class V students. The data analysis technique uses the t test and average results. The research results prove that there is a significant influence with an average pre-test of 55.00 and post-test of 77.22, and a significance value of 0.000 < 0.05 (significance level guidelines). Thus, it can be concluded that there is a positive and significant influence of the bamboo dance learning model on the ability to understand the contents of oral stories of class V students at SDN Mejoyolosari, Jombang Regency. ntents of oral stories of class V students at SDN Mejoyolosari Jombang Regency. The research sample was all 18 class V students. The data analysis technique uses the t test and average results. The research results prove that there is a significant influence with an average pre-test of 55.00 and post-test of 77.22, and a significance value of 0.000 < 0.05 (significance level guidelines). Thus, it can be concluded that there is a positive and significant influence of the bamboo dance learning model on the ability to understand the contents of oral stories of class V students at SDN Mejoyolosari, Jombang Regency.